Pelatihan Pijat Bayi Untuk Meningkatkan Kualitas Tidur Bayi di Kelurahan Kotamobagu - Hafsia KN Mokodompit; Dede H Gobel; Ayu S Bella; Della A Mursali; Fara D Makalalag; Fira W Supu; Sherly Tulengkey; Moh Rasyid Kuna (Kreativasi : Journal of Community Empowerment, 2024)
Baby massage is a type of stimulation that is carried out by gently stroking the surface of the baby's skin with the hands, with the aim of affecting the muscles, respiratory system, nerves, blood circulation and spleen. This is a relatively safe, cheap and easy to apply option to increase growth. and your baby's development. The aim of this service is to educate mothers who have babies about the health benefits of baby massage to improve the quality of their baby's sleep naturally. The method of service activities is lectures and exercises. The place is the residence of the mother who gave birth to her baby in RT 8 Kelurahan Kotamobagu, West Kotamobagu District. From the results of the activity, it is known that knowledge about the benefits of baby massage for the health and quality of baby sleep has increased, especially among mothers who have babies. Through lectures and practice of baby massage, we hope that mothers with babies can increase their knowledge and skills so you can do your own baby massage on babies and children.